Resilience and quality of life in patients with head and neck cancer (Research, Society and Development, 2022)
Objectives: To compare resilience and quality of life scores in patients with squamous cell carcinoma of the head and neck (HSCC) undergoing surgical treatment at different times of treatment and to correlate these variables. Methods: This is a cohort study with a quantitative approach, developed with 28 patients diagnosed with HNSCC, submitted to surgical treatment and followed up preoperatively (T1), four to six weeks (T2) and six months after the end of the procedure. treatment (T3). The Mini Mental State Examination (MMSE), the Resilience Scale and the UW-QOL quality of life questionnaire were applied at the three moments. Results: Comparing resilience and its domains at the three times, there was no significant difference. Regarding QoL, a significant difference was observed in the physical function domain, when T1 and T2 were compared. There was a positive correlation between resilience and depression. Conclusion: Given the correlation found, it is suggested that the variables studied be analyzed in this group of patients at the time of diagnosis, allowing the team to outline tactics to increase resilience, quality of life and contribute to the success of treatment and prognosis.